Operationalizing the analytical construct of contextualization - Nilsson, Per (NOMAD Nordic Studies in Mathematics Education, 2009)
This article elaborates on the construct of contextualization, which constitutes a constructivist contextual view on learning. Principles of constructivism and contextualization are operationalized into a set of four analytical categories that teachers and researchers can use in organizing their thinking about teaching and learning mathematics. The categories are discussed and verified throughout the design and analysis of a classroom compatible learning activity, which is thought to promote probabilistic reasoning. The article discusses suggestions for developing the operationalization and, thus, encourages future efforts that further explore the explanatory power of contextualization and its analytical categories.